Phytochemical Screening, GC-MS Analysis, and Evaluating In Vivo Antitrypanosomal Effects of a Methanolic Extract of Garcinia kola Nuts on Rats - Fatihu Ahmad Rufa'i; Daniel Baecker; Muhammad Dauda Mukhtar (MDPI AG, 2023)
Trypanosomiasis is a serious disease that affects both humans and animals, causing social and economic losses. Efforts to find new therapeutic approaches are warranted to improve treatment options. Therefore, the purpose of this communication includes the phytochemical screening of a methanolic extract of Garcinia kola nuts and the in vivo evaluation of its biological activity against rats infected with Trypanosoma brucei brucei and treated with 4 different concentrations of the extract (0.01, 0.1, 1, and 10 mg/kg). Treatment with suramin served as a positive control, while the negative control received no drug. Since the general toxicity of the extract could be ruled out, efficacy was evaluated based on physiological changes, such as induction of trypanosome parasitemia, influence on body temperature, and body weight. Survival was assessed during this study. Physical parameters, behavioral characteristics, and various hematological indices were also monitored. Based on the (patho)physiological and behavioral parameters (e.g., no parasitemia, no increase in body temperature, an increase in body weight, no loss of condition, no alopecia, and no gangrene), the efficacy of the extract was evident, which was also confirmed by 100% survival, while in the negative control, all rats died during the observation period. Since overall very similar results were obtained as a result of treatment with the established suramin, the in vivo antitrypanosomal activity of a methanolic extract of G. kola nuts on rats can be demonstrated in this communication. This opens the way, for example, for further development of drug formulations based on this methanolic extract.